Effects of a dry-land strengthening exercise program with elastic bands following the Kabat D2 diagonal flexion pattern for the prevention of shoulder injuries in swimmers - Della Tommasina, Ivan; Trinidad-Morales, Alfonso; Martínez-Lozano, Pedro; González-de-la-Flor, Ángel; Del-Blanco-Muñiz, José Ángel (Frontiers in Physiology, 2023)
Background: During the repetitive execution of the swimming strokes, the muscles responsible for the internal rotations of the shoulders tend to become stronger compared to the muscles that oppose these movements. The aim of this study was to analyse the effect of a strengthening program for the shoulder rotator muscles using elastic band exercises in a diagonal Kabat pattern (D2 for flexion) in swimmers, to develop an effective, quick and easy-to-implement protocol for preventive training routines. Methods: A randomized controlled trial design was carried out. Internal and external rotation range of movement, isometric strength of the muscles responsible for internal and external rotation of the shoulder, scapular movements, was measured at the beginning of the study and after 8 weeks postintervention. A total of 22 male swimmers participated in the study and were randomly assigned to either an experimental group (n = 11) or a control group (n = 11). The experimental group underwent a 8-week shoulder-strength program using elastic bands, while the control group focused on aquatic training. Results: The strength-training program resulted in an improvement in the isometric strength of the muscles responsible for external rotation and a better balance between the shoulder rotator muscles in the experimental group. However, these improvements have not been significant (p > 0.05).The strengthening exercise program showed minimal improvement in shoulder rotation strength and range of motion. These findings suggest that the prescribed shoulder-strengthening exercise could be a quick-beneficial dry-land training option to improve external rotation shoulder strength or range of motion, but more studies with larger sample sizes and more weeks of treatment are needed to determine the efficacy of this protocol.